2014
DOI: 10.1038/nature14060
|View full text |Cite
|
Sign up to set email alerts
|

An anisotropic hydrogel with electrostatic repulsion between cofacially aligned nanosheets

Abstract: Machine technology frequently puts magnetic or electrostatic repulsive forces to practical use, as in maglev trains, vehicle suspensions or non-contact bearings. In contrast, materials design overwhelmingly focuses on attractive interactions, such as in the many advanced polymer-based composites, where inorganic fillers interact with a polymer matrix to improve mechanical properties. However, articular cartilage strikingly illustrates how electrostatic repulsion can be harnessed to achieve unparalleled functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
368
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 452 publications
(379 citation statements)
references
References 29 publications
6
368
0
Order By: Relevance
“…[60][61][62][63][64] Recently, Liu et al proposed the concept of embedding anisotropic electrostatic repulsions within nanocomposite hydrogels, generating new possibilities for fabricating anisotropic soft materials with highly ordered structures. [62] In their aligned hydrogel systems, negatively charged unilamellar TINSs aligned coaxially in a strong magnetic field, which maintained maximum electrostatic repulsion and thereby induced a quasicrystalline structural ordering over macroscopic length scales and with uniformly large face-to-face nanosheet separation (Figure 3a). This transiently induced structural order was rigidified by using light-triggered in situ vinyl polymerization.…”
Section: Magnetic Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…[60][61][62][63][64] Recently, Liu et al proposed the concept of embedding anisotropic electrostatic repulsions within nanocomposite hydrogels, generating new possibilities for fabricating anisotropic soft materials with highly ordered structures. [62] In their aligned hydrogel systems, negatively charged unilamellar TINSs aligned coaxially in a strong magnetic field, which maintained maximum electrostatic repulsion and thereby induced a quasicrystalline structural ordering over macroscopic length scales and with uniformly large face-to-face nanosheet separation (Figure 3a). This transiently induced structural order was rigidified by using light-triggered in situ vinyl polymerization.…”
Section: Magnetic Fieldsmentioning
confidence: 99%
“…[62] Researchers discovered that the resultant hydrogel deformed easily under shear forces that were applied parallel to the embedded nanosheets yet resisted compressive forces that were applied orthogonally, thereby enabling excellent directional isolation of vibrations. This reinforcement of hydrogels by using intrinsic ordered nanocomposite structures can make for exceptionally strong and elastomeric nanocomposites with properties that closely mimic those of articular cartilage.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…This is because the load transfer efficiency could be greatly enhanced by the nacre-like layered structure. In addition, Liu et al [67] demonstrated an anisotropic nanocomposite hydrogel with a cartilage-like layered architecture. A magnetic field was first applied to the N,N-dimethylacrylamidecan suspension with titanate nanosheets (TiNSs).…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…In addition to their pioneering study on double-network hydrogels, Gong et al developed ionic bond-based polyampholyte hydrogels that possess excellent robustness and viscoelasticity 6,[18][19][20][21] . Aida et al developed mechanically robust hydrogels by incorporating various nanocomposites [22][23][24] . The aforementioned research demonstrates the great potential of supramolecular chemistry to improve the mechanical properties and fatigue resistance of hydrogels.…”
Section: Introductionmentioning
confidence: 99%